Influence of sintering temperature on the structural, electrical and optical properties of SmSrNiO4+δ - Chauhan M.; Jha P.A.; Jha P.K.; Singh P. (My University, 2025)
In this present work, the influence of sintering temperature (1250 °C and 1275 °C) on the structural and electrical properties of the layered perovskite structured Ruddlesen-Popper class of material SmSrNiO4+δis studied. The samples are synthesized in single-phase, and tetragonal phase with I4/mmm symmetry is suggested through Rietveld refinement. The microstructural studies reveal the increase in grain size with sintering temperature. The optical studies reveal that the bandgap of the material increases with the increase in sintering temperature. © 2020 Author(s).